Green low-carbon recyclable biomass filter material
By combining industrial solid waste such as coal gangue with biomass materials, green and low-carbon biomass filter materials are prepared, which solves the problems of environmental pollution and resource consumption in the production process of ceramic filter materials, and realizes the recycling of coal gangue and the high economic value of filter materials.
Patent Information
- Application Number
- CN202411655129.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The existing ceramic filters have problems such as environmental pollution, large resource consumption and poor pressure resistance during the production process. As industrial solid waste, coal gangue has been stored and occupied land for a long time and has caused pollution to the environment.
By mixing raw materials such as coal gangue, iron tailings, fly ash, rice husk powder, coconut bran, eggshell powder, corn starch, expanded vermiculite tailings and sodium alginate talc powder composite materials, it is stirred and pelleted , sintering and other processes to prepare green, low-carbon, recyclable biomass filter materials.
The recycling of coal gangue has been realized. The filter material produced has green and environmental protection, low carbon emissions and high economic value. It can be recycled as construction aggregate after use, reducing environmental pollution and resource consumption.
Smart Images

Figure BDA0005141938790000071 
Figure BDA0005141938790000091 
Figure BDA0005141938790000101
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water treatment, and in particular relates to a green, low-carbon and recyclable biomass filter material. Background Art
[0002] Ceramic granule filter material is a common water treatment material with a rough surface, light weight, high porosity, large specific surface area, and stable chemical properties. Compared with organic fillers, it has the advantages of strong biological attachment ability, good biofilm performance, easy backwashing, and strong pollution interception ability. The ceramsite filter material currently on the market is basically made of shale, clay, sludge, etc. as raw materials, and is prepared into granular filter media through processes such as crushing, screening, molding and sintering. Shale ceramsite requires mining of mineral resources, which has a certain impact on the environment; clay ceramsite has poor pressure resistance and is prone to breakage; sludge ceramsite has low cylinder pressure strength.
[0003] Gangue is an industrial solid waste generated during coal mining and washing. It is a black-gray rock associated with coal seams during the coalification process. It has a low carbon content and is harder than coal. As one of the largest industrial solid wastes in my country, the annual emission is equivalent to one-tenth of the coal production. The long-term storage and accumulation of gangue occupies a large amount of land. At the same time, after long-term weathering, gangue will form dust, which will increase the concentration of dust particles around the yard and pollute the local atmospheric environment. The existing harmful substances will enter the local water system with rainwater, which will pollute the water quality environment and have an adverse effect on carbon peak and carbon neutrality. At present, a variety of ways to utilize gangue resources have been proposed, such as preparing calcined kaolin, power generation, ceramic microbeads, fiber materials and silica aerogels. In order to realize the high-value utilization of gangue and turn waste into treasure, it is necessary to reasonably design it according to the composition and structural characteristics of gangue and produce products with high added value.
[0004] Gangue has a porous structure and can effectively absorb heavy metal ions in wastewater. It can treat solid waste and liquid waste with gangue, protect the environment, and has good economic application potential. Gangue can be processed into ceramsite with a certain pore structure and specific surface area. Using gangue to produce ceramsite filter material can increase the utilization value of gangue in sewage treatment, sewage purification and other ecological restoration fields. Summary of the invention
[0005] The purpose of the present invention is to provide a green, low-carbon and recyclable biomass filter material to achieve the recycling of coal gangue.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] The present invention provides a green, low-carbon and recyclable biomass filter material, characterized in that, by weight, the raw materials of the filter material include: 60-90 parts of coal gangue, 5-20 parts of iron tailings, 1-15 parts of fly ash, 1-5 parts of biomass filler, 6-10 parts of pore former, 2-8 parts of binder, 0.5-2 parts of bulking agent, and 1-4 parts of lubricant;
[0008] The preparation steps of the filter material are as follows:
[0009] Step 1: Coal gangue and iron tailings are roughly crushed and dried, and then ground and sieved through a 200-mesh sieve. The sieved coal gangue, iron tailings, fly ash, biomass filler, pore former and binder are put into a mixer and stirred to obtain a primary mixture;
[0010] Step 2: Add water to the primary mixture, stir and mix, then add a bulking agent, and stir to obtain a secondary mixture;
[0011] Step 3: putting the secondary mixed material into a granulator for granulation to obtain raw material balls;
[0012] Step 4: Spray the lubricant on the surface of the raw material ball, and form a lubricating layer after preliminary drying. The lubricating layer formed on the surface of the raw material ball can reduce friction and reduce wear rate;
[0013] Step 5: Put the raw material balls after preliminary drying into a rotary kiln for sintering, and obtain filter material after cooling.
[0014] Furthermore, the biomass filler includes rice husk powder and coconut bran in a mass ratio of 4:1, the particle size of the rice husk powder is 10-100 μm, and the particle size of the coconut bran is 50-200 μm.
[0015] Coal gangue is a recycled aggregate with a low carbon content. Rice husk powder is a by-product of rice husk processing. Coconut bran is an organic medium that falls off during the processing of coconut shell fibers. It has the characteristics of natural degradation and is purely natural and environmentally friendly. Both rice husk powder and coconut bran are light, have high porosity and are biodegradable.
[0016] Furthermore, the pore-forming agent is eggshell powder, and the particle size of the eggshell powder is 10-100 μm;
[0017] The binder is corn starch, the protein mass fraction of the corn starch is less than 1%, and the particle size is 1-100 μm.
[0018] Eggshell powder is a powdered product made by grinding discarded eggshells. Its main component is calcium carbonate, which decomposes and produces carbon dioxide during high-temperature heating and has a pore-forming effect.
[0019] The protein content in corn starch will affect the stability of its bonding force. When the protein content exceeds 1%, gelation will occur if the starch is mixed with water and stored for too long.
[0020] Furthermore, the bulking agent is expanded vermiculite tailings, and the preparation steps are as follows:
[0021] The vermiculite tailings are crushed and ground, passed through a 200-mesh sieve, placed in a crucible and placed in a heating furnace, heated to 500° C. at 30° C. / min, kept warm for half an hour, cooled, ground and passed through a 200-mesh sieve to obtain expanded vermiculite tailings;
[0022] The mass fraction of magnesium oxide in the vermiculite tailings is 20-25%.
[0023] Vermiculite tailings are waste generated during the mining and processing of vermiculite. They are hydrous silicate minerals and are natural minerals with the characteristics of high porosity, large specific surface area and low cost. They have large adsorption capacity, are non-toxic and harmless to the environment and are easy to regenerate. In addition to a large amount of water between structural units in vermiculite, there is also a portion of water in the structural unit layer. This portion of water exists in the form of structural hydroxyl groups and will be released when heated at high temperatures. Vermiculite has special expansion properties during the sintering and dehydration process, which can form a loose pore structure inside the material and improve the adsorption performance. Due to the high expansion rate of vermiculite tailings, the volume expansion rate can reach 18 times. If it is directly added to the material, it will cause deformation and cracking due to excessive expansion during heating. The vermiculite tailings should be partially expanded before being added to the material to achieve appropriate expansion and avoid material cracking.
[0024] Furthermore, the lubricant is a composite material of sodium alginate and talcum powder, the mass ratio of sodium alginate to talcum powder is 1:1-3, and the specific preparation steps are as follows:
[0025] Sodium alginate is dissolved in water at a mass fraction of 0.5%, talcum powder is added, and the mixture is evenly mixed and stirred by ultrasonic mixing to form a slightly viscous liquid to obtain a lubricant.
[0026] Further, the M / G ratio of the sodium alginate is 2.5-3.0, and the degree of polymerization of the sodium alginate is 100-300;
[0027] The talcum powder is fine talcum powder, the cumulative percentage of particles smaller than 20 μm is greater than 85%, and the mass fraction of calcium carbonate in the talcum powder is 1-2%.
[0028] Sodium alginate is mainly composed of β-D-mannuronic acid (M unit) and α-L-guluronic acid (G unit) connected by glycosidic bonds. In the molecular structure of sodium alginate, the ratio of M unit to G unit (i.e., M / G ratio) has a significant effect on the performance of sodium alginate. Sodium alginate with a higher M / G ratio has better elasticity and lower brittleness. The viscosity of sodium alginate solution varies with the molecular weight of sodium alginate. The higher the degree of polymerization of sodium alginate, the larger the molecular weight, and the greater the viscosity at the same concentration. The solution viscosity formed by sodium alginate with a higher degree of polymerization is too high, which is not conducive to the uniformity of spraying.
[0029] The calcium carbonate content in talcum powder cannot be too high, as the calcium ions in calcium carbonate will cross-link with sodium alginate to form gel, reducing the fluidity of the lubricant. Talc powder can fill the depressions on the surface of the material, reduce the surface roughness, and thus reduce the friction between them. Talc powder will decompose when the temperature exceeds 800°C, and its lubrication performance will be significantly reduced.
[0030] Ultrasonic mixing can utilize ultrasonic cavitation to rapidly collapse bubbles in the lubricant, generate huge stress, reduce the particle size in the lubricant, and obtain a uniformly mixed lubricant.
[0031] Furthermore, the mass of water added in step 2 is 10-20% of the primary mixture.
[0032] Furthermore, the diameter of the raw material ball is 2-16 mm.
[0033] Furthermore, the temperature of the preliminary drying is 40-50°C.
[0034] Furthermore, the rotary kiln comprises a preheating zone and a calcining zone. The preheating zone is heated to 800° C., the residence time of the raw material balls in the preheating zone is 1 hour, the calcining zone is heated to 1200° C., and the residence time of the raw material balls in the calcining zone is 30 minutes.
[0035] Beneficial effects of the present invention:
[0036] (1) Solid waste coal gangue, iron ore tailings and fly ash are used as the main raw materials, and light and degradable rice husk powder and coconut bran are added as biomass fillers. Eggshells are added as pore-forming agents, corn starch is used as a binder, vermiculite tailings are used as a bulking agent, and sodium alginate and talcum powder are used as lubricants. Solid waste and natural materials are fully utilized to sinter and prepare filter materials, so as to achieve the recycling of waste materials. The produced filter materials are green and environmentally friendly, and after use, the filter materials can be recycled as building aggregates.
[0037] (2) The material temperature of the filter material gradually rises in the preheating zone of the rotary kiln. The bonding effect of water will gradually weaken as the water evaporates. With the rolling operation, the wear and breakage of the ball is most likely to occur at this time, which will produce a large amount of powder, easily form large lumps, and in severe cases, the kiln will be blocked, affecting production efficiency. The lubricant is prepared by mixing sodium alginate and talcum powder. After spraying and drying, a lubricating layer is formed on the surface of the raw ball, which can reduce the wear and breakage during the heating process of the preheating zone. In the calcining zone, sodium alginate will be completely carbonized under high temperature conditions, and talcum powder will decompose. At this time, the solid phase reaction of the ball begins, the attraction between particles is enhanced, the retention force of the ball is improved, and the surface wear and breakage during the sintering process is greatly reduced. The surface roughness of the filter material prepared by this method is small, and the wear rate and breakage rate of the finished filter material are reduced. DETAILED DESCRIPTION
[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] Example 1
[0040] Preparation of expanded vermiculite tailings: crush and grind vermiculite tailings (magnesium oxide mass fraction is 20-25%), pass through a 200-mesh sieve, put them in a crucible and put them into a heating furnace, heat them to 500° C. at 30° C. / min, keep them warm for half an hour, cool them, grind them through a 200-mesh sieve, and obtain expanded vermiculite tailings.
[0041] Example 2
[0042] Preparation of lubricant: Sodium alginate (M / G ratio of 2.5-3.0, degree of polymerization of 100-300) is dissolved in water at a mass fraction of 0.5%, talcum powder is added according to the mass ratio of sodium alginate and talcum powder (calcium carbonate mass fraction of 5%-10%, the cumulative percentage of particle size less than 20 μm is greater than 85%) of 1:1, and ultrasonic mixing is performed to form a slightly viscous liquid after uniform stirring. The ultrasonic power is 200 W, the ultrasonic wave is performed for 4 seconds, the interval is 2 seconds, and the ultrasonic wave is continued for 20 minutes to obtain the lubricant.
[0043] Example 3
[0044] The difference from Example 2 is that the mass ratio of sodium alginate and talc in the lubricant is adjusted to 1:2.
[0045] Example 4
[0046] The difference from Example 2 is that the mass ratio of sodium alginate and talc in the lubricant is adjusted to 1:3.
[0047] Example 5
[0048] This embodiment provides a green, low-carbon, recyclable biomass filter material. The raw materials of the filter material include, by weight: 60 parts of coal gangue, 20 parts of iron tailings, 15 parts of fly ash, 0.8 parts of rice husk powder (particle size of 10-100 μm), 0.2 parts of coconut bran (particle size of 50-200 μm), 6 parts of eggshell powder (particle size of 10-100 μm), 2 parts of corn starch (protein mass fraction <1%, particle size of 1-100 μm), 0.5 parts of expanded vermiculite tailings prepared in Example 1, and 1 part of lubricant prepared in Example 2. The preparation steps of the filter material are as follows:
[0049] Step 1: Coal gangue and iron tailings are roughly crushed and dried, and then ground and sieved through a 200-mesh sieve. The sieved coal gangue, iron tailings, fly ash, rice husk powder, coconut bran, eggshell powder and corn starch are put into a mixer according to the above proportions and stirred to obtain a primary mixture;
[0050] Step 2, adding water to the primary mixture, the mass of the added water being 10% of the primary mixture, stirring and mixing for 30 minutes, and then adding the expanded vermiculite tailings prepared in Example 1, and stirring for 10 minutes to obtain a secondary mixture;
[0051] Step 3: Put the secondary mixture into a granulator for granulation to obtain raw material balls with a diameter of 2-16 mm;
[0052] Step 4: Spray the lubricant on the surface of the raw material ball and preliminarily dry it at 40°C for 10 hours to form a lubricating layer;
[0053] Step 5. Put the raw balls after preliminary drying into the rotary kiln for sintering. Set the pre-heating zone of the rotary kiln to 800°C, the residence time of the raw balls in the pre-heating zone is 1h, the calcining zone is heated to 1200°C, the residence time of the raw balls in the calcining zone is 30min, and the high-efficiency cooler is cooled to below 80°C to obtain the filter material.
[0054] Embodiment 6-7
[0055] The difference from Example 5 is that the ratio of raw materials is different, the specific ratio is shown in Table 1, and the other steps and conditions are the same as Example 3.
[0056] Table 1
[0057]
[0058] Example 8
[0059] The difference from Example 6 is that the mass fraction of the lubricant in the raw material is increased to 3 parts, and the other steps and conditions are the same as Example 6.
[0060] Example 9
[0061] The difference from Example 6 is that the mass fraction of the lubricant in the raw material is increased to 4 parts, and the other steps and conditions are the same as Example 6.
[0062] Example 10
[0063] The difference from Example 8 is that the lubricant prepared in Example 3 is used in the raw material to replace the lubricant prepared in Example 2, and the other steps and conditions are the same as Example 8.
[0064] Embodiment 11
[0065] The difference from Example 8 is that the lubricant prepared in Example 4 is used in the raw material to replace the lubricant prepared in Example 2, and the other steps and conditions are the same as Example 8.
[0066] Comparative Example 1
[0067] Compared with Example 5, the difference is that the raw material of this comparative example is directly the vermiculite tailings that are crushed, ground and passed through a 200-mesh sieve, without expansion treatment, and the other steps and conditions are the same as those of Example 5.
[0068] Comparative Example 2
[0069] Compared with Example 5, the difference is that in the preparation step of this comparative example, the expanded vermiculite tailings are synchronously mixed with other raw materials to form a primary mixture, and the specific steps are as follows:
[0070] Step 1, the gangue and iron tailings are roughly crushed and dried, and then ground and sieved through a 200-mesh sieve. According to the raw material ratio in Example 5, the sieved gangue, iron tailings, fly ash, rice husk powder, coconut bran, eggshell powder, corn starch and expanded vermiculite tailings are put into a mixer and stirred to obtain a primary mixture;
[0071] Step 2: Add water to the primary mixture, the mass of the added water being 10% of the primary mixture, and stir and mix for 40 minutes to obtain a secondary mixture;
[0072] Step 3: Put the secondary mixture into a granulator for granulation to obtain raw material balls with a diameter of 2-16 mm;
[0073] Step 4: Spray the lubricant on the surface of the raw material ball and preliminarily dry it at 40°C for 10 hours to form a lubricating layer;
[0074] Step 5. Put the raw balls after preliminary drying into the rotary kiln for sintering. Set the pre-heating zone of the rotary kiln to 800°C, the residence time of the raw balls in the pre-heating zone is 1h, the calcining zone is heated to 1200°C, the residence time of the raw balls in the calcining zone is 30min, and the high-efficiency cooler is cooled to below 80°C to obtain the filter material.
[0075] Comparative Example 3
[0076] Compared with Example 5, the difference is that no lubricant is added to the raw materials of this comparative example. Calculated by mass, the raw materials for the filter material provided in this comparative example include: 60 parts of coal gangue, 20 parts of iron tailings, 15 parts of fly ash, 0.8 parts of rice husk powder (particle size of 10-100 μm), 0.2 parts of coconut bran (particle size of 50-200 μm), 6 parts of eggshell powder (particle size of 10-100 μm), 2 parts of corn starch (protein mass fraction <1%, particle size of 1-100 μm) and 0.5 parts of expanded vermiculite tailings prepared in Example 1.
[0077] The steps for preparing the filter material are as follows:
[0078] Step 1: Coal gangue and iron tailings are roughly crushed and dried, and then ground and sieved through a 200-mesh sieve. The sieved coal gangue, iron tailings, fly ash, rice husk powder, coconut bran, eggshell powder and corn starch are put into a mixer according to the above proportions and stirred to obtain a primary mixture;
[0079] Step 2, adding water to the primary mixture, the mass of the added water being 10% of the primary mixture, stirring and mixing for 30 minutes, and then adding the expanded vermiculite tailings prepared in Example 1, and stirring for 10 minutes to obtain a secondary mixture;
[0080] Step 3: Put the secondary mixture into a granulator for granulation to obtain raw material balls with a diameter of 2-16 mm;
[0081] Step 4: put the raw material balls into the rotary kiln for sintering. Set the pre-zone of the rotary kiln to 800°C, the residence time of the raw material balls in the pre-zone is 1h, the calcination zone is heated to 1200°C, the residence time of the raw material balls in the calcination zone is 30min, and the high-efficiency cooler is cooled to below 80°C to obtain the filter material.
[0082] The filter materials prepared in Examples 5 to 11 and Comparative Examples 1 to 3 were tested for performance, and the results are shown in Table 2.
[0083] The physical properties of the filter material are tested in accordance with the reference standard "CJ / T299-2008 Artificial Ceramic Filter Material for Water Treatment".
[0084] Filter performance test of filter media:
[0085] Take 1t of sewage plant wastewater, of which COD concentration is 750mg / L, BOD concentration is 635mg / L, ammonia nitrogen concentration is 207mg / L, pH=7, and use a steel filter tank for filtration. The tank body has a diameter of 2 meters and a height of 3 meters. The tank is equipped with an inlet water distribution device and an outlet water collection device to ensure uniform distribution of water flow. The filter material is placed in the filter material layer in the tank. The filter material layer is 1 meter high. A pebble support layer is set at the bottom of the filter material layer. The particle size is 2-4cm and the thickness is 0.3 meters. It plays a role in supporting the filter material and preventing the loss of the filter material. The filtration speed is 8m / h, the backwash cycle is 24 hours, and air-water combined backwashing is used. The water backwashing intensity is 12L / s·m 2 , air backwash intensity is 15L / s·m 2 After filtering through filter materials, the COD concentration, BOD concentration and ammonia nitrogen concentration in the sewage are tested.
[0086] Table 2
[0087]
[0088]
[0089] As can be seen from Table 1, in Examples 5 to 7, the proportions of various components in the raw materials of the filter material are different. As the proportion of biomass filler increases, the porosity of the filter material increases, but too much biomass filler will lead to a loose structure of the filter material, and the sum of the breakage rate and the wear rate increases. Among them, the filter material prepared by the ratio of Example 6 has better comprehensive performance. Based on Example 6, Examples 8 and 9 increase the amount of lubricant added. The more lubricant, the thicker the lubricating layer formed, the better the protective performance, and the sum of the breakage rate and the wear rate decreases, but the talcum powder in the lubricant will fill the pores in the filter material, resulting in a slight decrease in the porosity and specific surface area, and a slight decrease in the sewage treatment performance. Embodiment 10 and embodiment 11 adjust the sodium alginate and talcum powder mass ratio in lubricant on the basis of embodiment 8, talcum powder accounts for an increased proportion in embodiment 10, and its lubrication performance is better, and the sum of breakage rate and wear rate is smaller than embodiment 8, and in embodiment 11, due to excessive talcum powder, the bonding performance of lubricant decreases, adhesion decreases, surface roughness improves, and lubrication effect deteriorates instead. In comparative example 1, vermiculite tailings are not expanded and added to the mixture, and the filter material prepared by it causes cracking due to excessive expansion, and its breakage rate and wear rate are significantly improved, resulting in direct passage through the crack during sewage filtration, and filtration performance is reduced. The expanded vermiculite tailings in comparative example 2 are synchronously mixed with other raw materials to form a primary mixture, and compared with embodiment 5, the expanded vermiculite tailings have a long contact time with water, and can absorb water to fill the interlayer space, and can expand again after heating, resulting in an increase in the cracking probability of the filter material, and the breakage rate will also increase accordingly. When no lubricant is used for the filter material in Comparative Example 3, the damage caused by adding it into the rotary kiln during sintering will greatly affect the sewage treatment performance.
[0090] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0091] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A green, low-carbon, recyclable biomass filter material, characterized in that: The raw materials of the filter material include, by weight: 60-90 parts of coal gangue, 5-20 parts of iron tailings, 1-15 parts of fly ash, 1-5 parts of biomass filler, 6-10 parts of pore former, 2-8 parts of binder, 0.5-2 parts of bulking agent, and 1-4 parts of lubricant; The preparation steps of the filter material are as follows: Step 1: Coal gangue and iron tailings are roughly crushed and dried, and then ground and sieved through a 200-mesh sieve. The sieved coal gangue, iron tailings, fly ash, biomass filler, pore former and binder are put into a mixer and stirred to obtain a primary mixture; Step 2: Add water to the primary mixture, stir and mix, then add a bulking agent, and stir to obtain a secondary mixture; Step 3: putting the secondary mixed material into a granulator for granulation to obtain raw material balls; Step 4: Spray the lubricant on the surface of the raw material ball and form a lubricating layer after preliminary drying; Step 5: Put the raw material balls after preliminary drying into a rotary kiln for sintering, and obtain filter material after cooling.
2. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The biomass filler comprises rice husk powder and coconut bran in a mass ratio of 4:
1. The particle size of the rice husk powder is 10-100 μm, and the particle size of the coconut bran is 50-200 μm.
3. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The pore-forming agent is eggshell powder, and the particle size of the eggshell powder is 10-100 μm; The binder is corn starch, the protein mass fraction of the corn starch is less than 1%, and the particle size is 1-100 μm.
4. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The bulking agent is expanded vermiculite tailings, and the preparation steps are as follows: The vermiculite tailings are crushed and ground, passed through a 200-mesh sieve, placed in a crucible and placed in a heating furnace, heated to 500° C. at 30° C. / min, kept warm for half an hour, cooled, ground and passed through a 200-mesh sieve to obtain expanded vermiculite tailings; The mass fraction of magnesium oxide in the vermiculite tailings is 20-25%.
5. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The lubricant is a composite material of sodium alginate and talcum powder, the mass ratio of sodium alginate to talcum powder is 1:1-3, and the specific preparation steps are as follows: Sodium alginate is dissolved in water at a mass fraction of 0.5%, talcum powder is added, and the mixture is evenly mixed and stirred by ultrasonic mixing to form a slightly viscous liquid to obtain a lubricant.
6. The green, low-carbon, recyclable biomass filter material according to claim 5, characterized in that: The M / G ratio of the sodium alginate is 2.5-3.0, and the degree of polymerization of the sodium alginate is 100-300; The talcum powder is fine talcum powder, the cumulative percentage of particles smaller than 20 μm is greater than 85%, and the mass fraction of calcium carbonate in the talcum powder is 5-10%.
7. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The mass of water added in step 2 is 10-20% of the primary mixture.
8. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The diameter of the raw material ball is 2-16 mm.
9. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The temperature of the preliminary drying is 40-50°C.
10. The green, low-carbon, recyclable biomass filter material according to claim 1, characterized in that: The rotary kiln comprises a preheating zone and a calcining zone. The preheating zone is heated to 800° C., the residence time of raw material balls in the preheating zone is 1 hour, the calcining zone is heated to 1200° C., the residence time of raw material balls in the calcining zone is 30 minutes.
Citation Information
Patent Citations
Ceramsite prepared from high-silicon fine iron tailings and preparation method thereof
CN101967063A
Biological ceramisite filter material made of vulcanized lead zinc ore flotation tailings, and preparation method thereof
CN103086741A
Method for improving large amount of red mud soil and method for burning haycite from improved red mud
CN105414146A
Preparation method of honeycomb ceramic filter body for gasoline engine and the honeycomb ceramic filter body
CN110483094A
Wall flow type honeycomb ceramic filter with adjustable porosity and preparation process thereof
CN115231913A
Cited By
Ceramsite filter material based on Yellow River sediment and preparation method thereof
CN122355729A